2013
DOI: 10.1002/jmv.23599
|View full text |Cite
|
Sign up to set email alerts
|

Serum prolactin levels and prolactin mRNA expression in peripheral blood mononuclear cells in hepatitis C virus infection

Abstract: Prolactin is not only a pituitary hormone but an immunoregulatory hormone secreted from lymphocytes. Prolactin induction in relation to hepatitis C virus (HCV) infection has not been elucidated. The serum levels of prolactin were examined in 232 HCV-infected subjects positive for anti-HCV antibody and 65 healthy controls negative for it, who were recruited in the cohort study. The prolactin mRNAs were measured in peripheral blood mononuclear cells (PBMCs) of eleven healthy volunteers including five men and six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A prospective study illustrated that high PRL serum level is observed in HCV-infected patients compared to the healthy controls due to induction of PRL mRNA in the peripheral blood mononuclear cells by HCV [51]. Glal et al observational study showed that high PRL serum level is linked with development of thrombocytopenia in patients with HCV infection as there was a negative correlation between PRL serum level and platelet counts [52].…”
Section: Role Of Prolactin In Viral Infectionmentioning
confidence: 99%
“…A prospective study illustrated that high PRL serum level is observed in HCV-infected patients compared to the healthy controls due to induction of PRL mRNA in the peripheral blood mononuclear cells by HCV [51]. Glal et al observational study showed that high PRL serum level is linked with development of thrombocytopenia in patients with HCV infection as there was a negative correlation between PRL serum level and platelet counts [52].…”
Section: Role Of Prolactin In Viral Infectionmentioning
confidence: 99%
“…Wallis showed that PRLRs could serve as a receptor and entry site for virus-host cell communication for CMV and other viruses such as rubella [54] . In addition, a prospective study showed increased PRL serum levels in patients with hepatitis C virus (HCV) compared with control groups, which was due to HCV induction of PRL mRNAs in PBMC [55] . Although this association does not include extrahepatic manifestations of HCV such as autoimmunity, hyperprolactinemia is associated with HCV [56] .…”
Section: Prolactin and Viral Infectionsmentioning
confidence: 99%